Uslub Amar dan Nahy: Dimensi Edukatif dalam Hadis Nabawi, Analisis Balaghah dan Implikasi bagi pembelajaran Bahasa Arab - Rifan Basahona; Nurfadillah; Haniah (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This article examines the uslūb amar (command style) and nahy (prohibition style) in educational-themed Prophetic hadiths through an integrative approach between balāghah and pragmatics, with the aim of revealing their meaning, communicative function, and pedagogical implications for Arabic language learning. This study uses a descriptive-analytical qualitative method on a number of selected hadiths containing the forms of amar and nahy, which are analyzed through the stages of identifying linguistic forms, interpreting rhetorical meanings based on the context of the utterance (maqām), and interpreting pragmatic functions as directive speech acts. The results of the study show that the meaning of amar and nahy in Prophetic hadiths is not singular and literal, but rather experiences an expansion of the meaning of figures of speech such as irsyād (guidance), nadb (advice), ta'dīb (education), and tahdzīr (warning), which are determined by the context of the situation, the relationship between the speaker and the interlocutor, and the purpose of communication. Prophet Muhammad SAW. consistently applies rhetorical strategies such as tikrar (repetition), muqābalah (contrastive parallelism), and istifhām inkārī (rhetorical questions) to create a profound persuasive-educative effect. These findings have significant implications for the development of Arabic language learning, including the integration of hadith texts as an authentic corpus, strengthening students' pragmatic awareness, value-based learning, designing dialogic activities, reconstructing a functional balāghah syllabus, and developing communicative performance-based assessments